Factors Important in Facial Plastic and Reconstructive Surgery Fellowship Program Selection - Lozada, Kirkland N.; Bloom, Jason D. (Facial Plastic Surgery, 2019)
Facial plastic and reconstructive surgery (FPRS) training programs offer exceptional exposure to the most current techniques in the field. However, applicants have many factors to weigh when ranking programs. Therefore, it is important to examine the factors that applicants believe to be the most critical when choosing an FPRS fellowship. This is an anonymous online survey of FPRS fellows between the years 2018 and 2020 (total 147). Respondents were asked to rate importance of program factors on a Likert scale (1–5). Of 147 applicants, 63 (43%) responded. Applicants found the type of practice, academic or private, equally important, with score averages of 3.02 and 3.25, respectively. The two most important program factors to applicants were exposure to the business of medicine/practice management (3.94) and location (3.4). The two most important areas of surgical exposure include rhinoplasty (4.54) and aging face (4.44). Of 63 applicants, 41 (65%) were interested in private practice, with 51% seeking a facial plastics/plastic reconstructive surgery group setting versus solo practice, general otolaryngology group, or dermatology group practice. Of 61 applicants, 48 (76%) wanted a mix of cosmetic/reconstructive surgery in their first 5 years of practice. Finally, applicants were not interested (average: 1.94) in keeping general otolaryngology as part of their practice. Applicants want strong exposure to the business of medicine, rhinoplasty, aging face, all while in their preferred location. Additionally, the majority of applicants seek employment in a plastic surgery focused group practice, with the sole focus being the breadth of FPRS.
Keywords: facial plastic surgery; fellowship; program selection; applicants